Peningkatan Produktivitas Mesin Twin Screw Extruder (TSE) Dengan Proses Heat Treatment Pada As Stang Cutting - Riki Candra Putra (TRAKSI, 2021)
The plastic manufacturing industry is one of the industries that uses a continuous production process to produce household needs made of plastic, one of the machines that can produce plastic with good capacity and quality is the twin screw extruder (TSE) machine. The component in the twin screw extruder (TSE) that functions as an intermediary between the motor and the cutting on the extruder machine is that the cutting handlebar is a component that must have properties that are hard, resilient, resistant to friction. VCN 150 steel is the material chosen for cutting axle components because it has good characteristics. How to get the performance of the cutting axle made from VCN 150 steel, it is necessary to do heat treatment. After the heat treatment process, it is necessary to test the characteristics of the cutting axle material. To find out the results of the heat treatment process as cutting, tests are carried out related to capacity, cycle time, reject and resistance to cutting friction. The results of the material hardness characteristics test resulted in an average hardness of 39.6 HRC and an average hardness of 50.6 HRC after heat treatment. The results of the chemical composition test resulted, the carbon content contained in the as cutting was 0.402%, with the result that as cutting was included in the medium carbon steel group. In field testing, the new cutting axle was able to reduce cycle times by 40 minutes during one year of operation. For the capacity of hot cut dies to reduce the reject rate by 12 kg and a decrease in performance against friction resistance, the axle cutting can reduce the replacement rate by 4 times. Overall, hot cut treatment dies can reduce cycle time, reject, and replace cutting axles.